Barriers and Facilitators to Dental Care Services Utilization Among Children With Disabilities: A Systematic Review and Thematic Synthesis - Shiamaa Al‐Mashhadani; Mona Nasser; Anas Alsalami; Lorna Burns; Martha Paisi (Wiley, 2024)
ABSTRACT Background This systematic review investigates barriers and enablers to dental care utilization by disabled children. Given the high global prevalence of disabilities in children, coupled with poor oral hygiene and a 45% rate of dental caries in this group, developing inclusive oral health strategies is critical. The review aims to synthesize literature on factors affecting oral healthcare improvement for disabled children, identifying barriers, facilitators and knowledge gaps. Methods The review was conducted following the Joanna Briggs Institute's methods and reported according to PRISMA guidelines. A comprehensive search spanned multiple databases, considering perspectives from carers, parents, dentists and health professionals. The focus was on studies involving children up to age 17 with disabilities, as defined by WHO, using dental care services. Exclusions included non‐qualitative studies, populations over 18 and nondisabled children. There were no restrictions on publication date or language. Thematic synthesis of the studies extracted themes related to barriers and enablers in oral healthcare for disabled children. Results Thematic synthesis identified five overarching themes: stigma, communication issues, professional development, oral health education and medical‐dental collaboration. Facilitators included enhancing accessibility and availability of dental care through a holistic approach, improving dental care facility environments and ensuring skilled dental care providers. Discussion The review underscores the importance of interprofessional collaboration, improved parent/caregiver education and specialized dental facilities to support children with disabilities. It identifies key barriers and facilitators in dental care, including challenging stereotypes, improving communication between providers and parents, enhancing holistic training and addressing gaps in oral health education and integrated healthcare systems. Conclusion Addressing the complex dynamics of dental care for disabled children is essential for developing inclusive and effective preventive and therapeutic strategies. This review highlights the need for tailored approaches and enhanced support systems to improve oral health outcomes in this vulnerable population. Patient and Public Contribution The members of the family support department, Middle East and North Africa (MENA) Organization for Rare Disease and Disability who provided the disability voice and contributed to providing input to the review protocol.